2011
DOI: 10.1002/joc.2134
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal change of soil moisture in Mongolia: its climatology and modelling

Abstract: Mongolia has an arid and cold climate due to its geographical settings of inland and mid-latitude highlands. The soil moisture varies seasonally, depending mainly on the balance of precipitation and evapotranspiration as well as on winter soil-freezing and spring snowmelt. Soil moisture climatology (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) for Mongolia is presented with a focus on three vegetation zones: the forest steppe, steppe, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…After mid-October, soil moisture was assumed to be constant when the daily air temperature was <0°C. This pattern of the soil moisture model generally corresponds with the pattern of precipitation in Mongolia (Xue 1996, Nandintsetseg & Shinoda 2011. So, the seasonal variation of the precipitation cycle suggested that the plant emergency may occur around the transition period from Phase I to Phase II, which was identified as late May to early June, if precipitation recharging lately or anomalously.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…After mid-October, soil moisture was assumed to be constant when the daily air temperature was <0°C. This pattern of the soil moisture model generally corresponds with the pattern of precipitation in Mongolia (Xue 1996, Nandintsetseg & Shinoda 2011. So, the seasonal variation of the precipitation cycle suggested that the plant emergency may occur around the transition period from Phase I to Phase II, which was identified as late May to early June, if precipitation recharging lately or anomalously.…”
Section: Discussionmentioning
confidence: 54%
“…Peaks of NDVI and EVI values, indicative of high photosynthetic and biomass accumulation, were found in late July to late August, which can be explained by being the period with the highest precipitation in Mongolia. Moreover, the occurrence of peak values was consistent with the peak of soil moisture during phase-2 (Nandintsetseg & Shinoda 2011). Around 85 percent of the precipitation falls in the warm period of the year between April and September, of which 50-60 percent is received in July-August (Natsagdorj et al 2005).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Annual average precipitation in this area is less than about 350 mm, but its interannual variation is large (Vandandorj et al 2015;Yu et al 2004), which is typical for drylands. Because precipitation and snowfall increase and temperature decreases from south to north (Morinaga et al 2003;Nandintsetseg and Shinoda 2011), vegetation correspondingly changes from desert to drylands and forest steppe ecosystems. Droughts and severe winters are a cause of high mortality among livestock (Fernandez-Gimenez et al 2012Tachiiri and Shinoda 2012) and wild animals (Kaczensky et al 2011a).…”
Section: Environments Of Mongolia's Gobi-steppe Ecosystemmentioning
confidence: 99%
“…The northernmost zone consists of taiga forest and forest steppe, while the southern region contains steppe, desert steppe, and desert. The northern part of Mongolia is covered by forested mountain ranges with a dry sub-humid climate, whereas the southern part encompasses the Gobi Desert at lower elevations with a drier climate (Nandintsetseg and Shinoda, 2011). In this study, we used monthly precipitation data collected from twelve stations well distributed across Mongolia during the period 1979-2013.…”
Section: Study Area and Datamentioning
confidence: 99%